Criminal Investigation of Serial Murders: Challenges and Solutions - Ali Rezei Gelvardi; Azade Sadeghi (پژوهشهای حقوقی)
Serial murder is a rare phenomenon in a rare type of crime (murder), but despite this, the process of criminal investigation of serial murder cases in Iran has always faced severe weaknesses and challenges, and in most cases, such as the murder case, In the serials of Mohammad Basijeh, Saeed Hanai and Farid Baghlani, the existence of a survivor of a crime has been the main factor in the discovery and arrest of the criminal. This research is applied in terms of purpose and descriptive-analytical in nature. In this research, first by using library tools (dissertation, article, etc) to collect information and extract data from available sources, then the sources are analyzed and conclusions are drawn. It comes The results of this research showed the role of psychologylegality and the necessity of the presence of a forensic psychologist alongside the crime scene analysis team in identifying the killer's motive, drawing his criminal profile and providing the appropriate interrogation technique, and using modern methods of criminal investigation such as criminal and geographic profiling, data technique The study and method of analyzing the link of the case is very important in the early arrest of the criminals of such crimes.